Establishing the Mezzaterra on Ritual and Myth: Ahdaf Soueifâ€™s Appropriation of the Sacred in â€œThe Map of Loveâ€ - van Deventer, Christine (WritingThreeSixty, 2018)
The Map of Love, by Egyptian author Ahdaf Soueif, is set in a space that is a cultural meeting ground. Ahdaf Soueif is described by many to be a "hybrid" writer as her work seeks to occupy a ground common to Arab and Western cultures alike. Soueif coined her own name for this concept. She calls it Mezzaterra, which translated means "middle ground". This paper is about how Soueif anchors the idea of Mezzaterra in the sacred realm at a point in the past that stretches beyond the origin of Christianity and Islam, by referencing the Egyptian Creation Myth of Isis, Osiris and Horus. In this way she establishes it as a reference for the legitimate acceptance and interrelatedness of the abovementioned religions and cultures. By using Mircea Eliade's Myth of the Eternal Return, I study how Soueif uses the repetition of the ritual in The Map of Love to confer a reality upon events. The reference to The Sacred and The Profane allows me to study how the sacred is shown to interact with the real in The Map of Love and how the real is placed on the same level as the sacred and thus made sacred, especially through the employment of a hierophany in the text. Thus the Mezzaterra is established as a sacred ideology that has its roots in Egypt's Creation Myth - the overarching and informing Creation Myth.